1989
DOI: 10.3109/00207458908991618
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of the Transcendental Mediation Technique and Progressive Muscle Relaxation on Eeg Coherence, Stress Reactivity, and Mental Health in Black Adults

Abstract: Eighty-three black college students, staff and adults were pretested on EEG coherence, skin potential (SP) habituation to a series of loud tones, psychometric measures of mental health (Tennessee Self-concept Empirical Scales and Spielberger State-Trait Anxiety Inventory) and IQ. They were then randomly assigned to one of the three treatment groups: the Transcendental Meditation technique (TM); Progressive Muscle Relaxation (PR); or cognitive-behavioral strategies (C). Approximately one year later, they were p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 78 publications
(49 citation statements)
references
References 36 publications
2
47
0
Order By: Relevance
“…This conclusion is in accordance with the findings of Gaylord [13], who reported that the coherence was higher in the frontal and central areas only during transcendental meditation practice relative to the closed eyes condition, but not during progressive muscle relaxation.…”
Section: Discussionsupporting
confidence: 82%
“…This conclusion is in accordance with the findings of Gaylord [13], who reported that the coherence was higher in the frontal and central areas only during transcendental meditation practice relative to the closed eyes condition, but not during progressive muscle relaxation.…”
Section: Discussionsupporting
confidence: 82%
“…These studies have shown increased EEG coherence during Transcendental Meditation (e.g. Gaylord et al, 1989;Levine, 1976;Travis and Orme-Johnson, 1989;Travis et al, 2002; experienced practitioners of Transcendental Meditation as well as novices showed increased alpha coherence compared to resting (Dillbeck and Bronson, 1981;Travis, 2001;Travis and Wallace, 1999). Zenmeditation reportedly increased alpha coherence in meditation novices (Murata et al, 2004).…”
Section: Introductionmentioning
confidence: 98%
“…Most often breathing techniques are used to minimize physiologic responses to stress, possibly by increasing parasympathetic response. 15 Also, they are often used in conjunction with relaxation techniques such as Jacobson's progressive muscular relaxation 16 and autogenic training. 17 A relatively simple respiration monitor that facilitates slowing one's breathing rate has been approved by the Food and Drug Administration for the reduction of blood pressure.…”
Section: Relaxation and Breathing Techniquesmentioning
confidence: 99%